Secondary Infection and Co-infection in COVID-19 Patients Receiving Tocilizumab - Çağla Erdoğan; Metin Kılınç; Beyza Şahin; Hülya Sungurtekin (Galenos Yayinevi, 2024)
Objective: Tocilizumab (TCZ) is a recombinant humanized anti-IL-6 receptor monoclonal antibody that is beneficial in critically ill COVID-19 patients. However, the clinical efficacy and safety of immunosuppressants (including tocilizumab, sarilumab and anakinra) in COVID-19 patients are not yet known. These treatments may predispose patients to infection. The aim of this study was to find any connection between the use of tocilizumab and increased secondary bacterial infections. Materials and Methods: In this study, we conducted retrospective analyses of secondary bacterial infections in COVID-19 patients in the intensive care unit. This study included patients with laboratory-confirmed COVID-19 infection or clinically and radiologically confirmed COVID-19 infections who were admitted to the university hospital adult ICUs between March 2020 and January 2022. Demographic data, recent exposure and travel history, clinical symptoms or signs, laboratory findings, and comorbidities were recorded. Microbial cultures from tracheal aspirates, blood, and urine were obtained at admission and throughout the hospital stay. The patients who received tocilizumab treatment noted and analyzed for seconder infections. Blood cultures were taken at least 48 h after the first dose of tocilizumab. Results: We found that 80 patients (%37) had positive culture samples at admission, and most of these cases were admitted to the ICU from various hospital wards. The analyzed data showed that the tocilizumab group had a higher incidence of positive culture samples (%75 vs %35, p=0,0001). The results showed that culture of tocilizumab taken patients had more incidence with metisilin resistance S. aureus, Klebsiella spp., and Acinetobacter spp. (p=0,0001). Infection and mortality rates were much higher than those in the usual care group. Conclusion: Secondary infections and sepsis are major risk factors for mortality. The pathogens detected were drug resistant and had a lower chance of treatment. The benefit of tocilizumab treatment was lost in these patients because of secondary infections. Future studies are needed to help determine the risks of tocilizumab treatments.